Evaluation of a Training Course for University Teachers - Rothman, A. I.; Robinson, Sarah (Canadian Journal of Higher Education, 1977)
This report describes the evaluation of a training course for university teachers offered by the University Teaching Methods Unit of the University of London Institute of Education. The procedures used required the collection of information from the course participants at the conclusion of the course and again after a four month interval. A post course ques- tionnaire asked the participants to assess the success of the course in achieving its stated objectives and to indicate the extent to which the course's scheduled activities contributed to the achievement of the course objectives. Cross tabulation of the results of the two lines of questions identified which course activities contributed to the achievement of specific objectives. The data collected four months later indicated the extent to which and in what areas participants felt the course did have significant impact on their teaching behaviours.